LITERATURE REVIEW: ANALYSIS OF THE IMPLEMENTATION OF THE PRINCIPAL’S LEADERSHIP STRATEGY IN IMPROVING TEACHER PERFORMANCE - Hoirotun Hoirotun; Intan Permatasari; Ali Gufron; Riskiyatin Riskiyatin; Miftahus Surur (STKIP PGRI Situbondo, 2025)
Schools are educational institutions that train the personality and develop students' intelligence as part of the intellectualization of the nation's life. Meanwhile, the principal is an educational employee who is competent and given the responsibility to run the school. This study aims to examine the principal's leadership strategies that can be implemented to improve teacher performance. This research uses the literature review method by reading, analyzing, and drawing conclusions. The literature review results are effective leadership strategies, such as instructional leadership. This leadership can encourage the development of teacher professionalism and contribute to the overall success of education.